Menopause Hubungan Pengetahuan Dan dukungan Keluarga Dengan Persiapan Ibu Menghadapai Menopause - Seska Anita Nahuway (Gema Bidan Indonesia, 2023)
Background. Menopause is a natural thing that occurs in women as they get older so that they experience a decrease in reproductive hormones followed by a decrease in ovarian function. A decrease in such hormones can result in physical and psychological symptoms. The purpose of this study was to analyze the relationship between family knowledge and support with maternal preparation for menopause in Rumahkay Village, Amalatu District.Methode.The type of research used is an analytical type of research with a cross-sectional approach. The population consisted of 143 people and samples taken with the Simple random sampling technique amounted to 105 people. Data were collected using questionnaires and analyzed using a chi square statistic.Result. From the results of the study, it was found that almost half of mothers in Rumahkay Village had a sufficient level of knowledge about menopause, while almost all mothers in rumahkay village received support from families in preparation for menopause. Almost all mothers in Rumahkay Village are ready to face menopause. The results of the analysis test found that there was a relationship between knowledge and maternal preparation for menopause and there was a relationship between family support and maternal preparation for menopause.Conclusion. The conclusion in this study is that there is a relationship between family knowledge and support with maternal preparation for menopause.Suggestion. It is hoped that the next investigator will be able to expand the research by adding other factors related to preparation for menopause so that the research results can be more accurate.